FAMILY SUPPORT AS AN EFFORT TO IMPROVE TUBERCULOSIS PATIENT RECOVERY: SYSTEMATIC REVIEW - Rumokoy, Christine Bernadette Maria; Rumokoy, Daniella Geertruida Maria (JURNAL KEPERAWATAN, 2026)
Background: Pulmonary tuberculosis (TB) remains a global concern. Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis. Family support is crucial for improving the health of TB patients. Objective: The purpose of this systematic review is to examine the relationship between family support and the recovery status of TB patients. Methods: The systematic review used three databases. A total of 20.291 articles were retrieved, with 13 articles meeting the criteria for analysis. Results: family support for pulmonary TB patients can improve their health. Conclusion: Therefore, increased family education is needed to provide optimal care for sick family members. The better the family’s knowledge, the better the family’s role will be fulfilled.